Potential Benefits of Pomegranate as an Additive in Fish Diet and Fish Products: A Review - Sarfraz, Meerub; Mahmood, Mamoona; Batool, Moazama; Ain, Qurat-UL-; Maalik, Sadia; Mushtaq, Sajida (BioScientific Review, 2024)
Pomegranate (Punica granatum), commonly known as “Anar”, is an ancient fruit. It is preferably consumed due to its pleasing taste and high nutritious value along with some other associated health benefits. These benefits are not only meant for human beings, however, also for the fish. In recent times, scientific interest in pomegranate and its consumption has increased due to its numerous health benefits. Therefore, the current study aimed to review the most recent literature on different properties of the pomegranate. These properties include antimicrobial and antioxidant activities, its effect on hematological and growth parameters along with the role of pomegranate as a preservative in fish and fish products. The current study evaluated previously conducted studies to determine the effect of pomegranate on different systems of fish. Results showed that the intake of pomegranate effectively increased the growth of juvenile fish and dietary value of fish, boosted the hematological and immune responses, as well as feed efficiency and antioxidant activity. Moreover, it also showed antioxidant properties and proved effective for the preservation of fish fillets by reducing lipid oxidation, chemical degradation, and microbial growth in stored fish. Therefore, the incorporation of pomegranate in fish food has numerous applications. However, additional research is required to ascertain the safe limits.